2019
DOI: 10.1007/s10157-019-01810-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of migalastat in a Japanese population: a subgroup analysis of the ATTRACT study

Abstract: Background Fabry disease is a progressive X-linked lysosomal disorder. In this subgroup analysis of the global phase III ATT RAC T study, the efficacy and safety of oral migalastat, a pharmacologic chaperone, were investigated in Japanese patients with Fabry disease. Methods Patients were randomly assigned to receive migalastat (150 mg every other day) or to continue biweekly enzyme replacement therapy infusions (ERT; agalsidase alfa 0.2 mg/kg or agalsidase beta 1.0 mg/kg) for 18 months followed by a 12-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…MEDLINE = Total n = 11, post analysis n = 2 [ 18 , 19 ]; 3 studies were excluded because they were preliminary reports of other studies [ 22 , 24 , 25 ]; 4 studies were excluded because they were sub-analysis of other studies [ 23 , 26 , 27 , 28 ] and 2 studies were excluded because they did not meet the inclusion criteria [ 29 , 30 ]. EMBASE = Total n = 0; SCOPUS = Total n = 0, Cochrane Total n = 0 and Google Academic = Total n = 191, post analysis n = 2 [ 20 , 21 ]; (11 studies were overlapped with MEDLINE, both included and excluded; 1 study was excluded because it was a preliminary report of other study [ 25 ], 1 study was excluded because it did not have renal biomarkers among its dependent variables [ 31 ]; 1 study was excluded because its sub-analysis of other studies [ 32 ]; 173 studies were excluded for not meeting inclusion criteria).…”
Section: Resultsmentioning
confidence: 99%
“…MEDLINE = Total n = 11, post analysis n = 2 [ 18 , 19 ]; 3 studies were excluded because they were preliminary reports of other studies [ 22 , 24 , 25 ]; 4 studies were excluded because they were sub-analysis of other studies [ 23 , 26 , 27 , 28 ] and 2 studies were excluded because they did not meet the inclusion criteria [ 29 , 30 ]. EMBASE = Total n = 0; SCOPUS = Total n = 0, Cochrane Total n = 0 and Google Academic = Total n = 191, post analysis n = 2 [ 20 , 21 ]; (11 studies were overlapped with MEDLINE, both included and excluded; 1 study was excluded because it was a preliminary report of other study [ 25 ], 1 study was excluded because it did not have renal biomarkers among its dependent variables [ 31 ]; 1 study was excluded because its sub-analysis of other studies [ 32 ]; 173 studies were excluded for not meeting inclusion criteria).…”
Section: Resultsmentioning
confidence: 99%
“…Left ventricular mass has been shown to be an important parameter for assessing the cardiac effects of the treatment in patients with FD [ 15 ]. Male patients with FD receiving PCT had an increase in leukocyte α-Gal A activity, while this was not confirmed in female patients with FD [ 16 ]. Therefore, it could be meaningful to measure the change in enzyme activity in WBC for monitoring the therapeutic effect of PCT in patients with FD.…”
Section: Discussionmentioning
confidence: 99%
“…The FACET study reported a decrease greater than 50% in interstitial inclusions in peritubular capillaries, a significant reduction in podocyte inclusions, and improved kidney function, regardless of baseline urinary protein levels, after six months of treatment 91 . In the ATTRACT randomized trial, migalastat and ERT had similar effect over kidney function 18 months into the study 92 , although migalastat increased α-GAL activity, stabilized kidney function, and kept plasma lyso-GL3 levels low in a subgroup of Japanese patients 93 . Another study also observed a decrease in podocyte deposits of GL3 after six months of treatment with migalastat 94 .…”
Section: Clinical Management Of Adult Patients With Fdmentioning
confidence: 93%